PENGARUH MANAJEMEN LABA RIIL TERHADAP TINGKAT KEPATUHAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lau, Serlina Kiik; Lasdi, Lodovicus (Jurnal Akuntansi Kontemporer, 2017)
The objective of this research is to test and analyse the effect of real earning management to level of compliance of disclo-sure corporate social responsibility. Factors that measured in the affect of corporate social responsibility is real earning manage-ment with three proxy (abnormal cash flow from operation, abnormal production costs, and abnormal discretionary expenses. The research is designed with quantitative approach with hypothesis. The data used is quantitative data in the form of information about CSR activity and financial statement. The research object is manufacturing company that is listed in Indonesia Stock Ex-change in 2013-2015. The data analysis technique that used in this research is multiple linear regression. The result of this re-search shows the abnormal cash flow from operation and abnormal discretionary expenses does not have significant effect to level compliance of disclosure corporate social responsibility. Abnormal production costs has significant positive effect to level compli-ance of disclosure corporate social responsibility, this is indicated by the mean value of abnormal production costs that positive, it’s showed real earning management through abnormal production costs. This shows that companies in Indonesia tends to increase profits through increased production that resulted to increased level of compliance of disclosure corporate social responsibility.